Ion-Exchange in Glass-Ceramics - Beall, George H.; Comte, Monique; Dejneka, Matthew J.; Marques, Paulo; Pradeau, Philippe; Smith, Charlene (Frontiers in Materials, 2016)
In the past few years ion-exchange in glasses has found a renewed interest with a lot of new development and research in industrial and academic labs and the commercialization of materials with outstanding mechanical properties. These glasses are now widely used in many electronic devices including hand-held displays and tablets. The exchange is generally conducted in a bath of molten salt below the transition temperature of the glass. The exchange at the surface of an alkali ion by a bigger one brings compressive stress at the surface. The mechanical properties are dependent on the stress level at the surface and the depth of penetration of the bigger ion. As compared to glasses, glass-ceramics have the interest to display a wide range of aspects (transparent to opaque) and different mechanical properties (especially higher modulus and toughness). There has been little research on ion-exchange in glass-ceramics. In these materials the mechanisms are much more complex than in glasses because of their polyphasic nature: ion-exchange generally takes place mostly in one phase (crystalline phase or residual glass). The mechanism can be similar to what is observed in glasses with the replacement of an ion by another in the structure. But in some cases this ion-exchange leads to microstructural modifications (for example amorphisation or phase change). This article reviews these ion-exchange mechanisms using several transparent and opaque alumino-silicate glass-ceramics as examples. The effect of the ion exchange in the various glass-ceramics will be described, with particular emphasis on flexural strength.